Developing a Core Outcome Set for the Evaluation of Antibiotic Use in Prelabor Rupture of Membranes: A Systematic Review and Semi-Structured Interview - Liu, Dan; Wu, Lin; Luo, Jiefeng; Li, Siyu; Liu, Yan; Zhang, Chuan; Zeng, Linan; Yu, Qin; Zhang, Lingli (Frontiers in Pharmacology, 2022)
Background: Prelabor rupture of membranes (PROM) is associated with maternal and neonatal infections. Although guidelines suggest prophylactic antibiotics to pregnant women with PROM, the optimal antibiotic regimen is still controversial. It’s difficult to synthesize the data from different studies as the variation in reported outcomes. Objective: To form the initial list of outcomes for the core outcome set (COS) for the evaluation of antibiotic use in PROM by identifying all existing outcomes and patients’ views. Methods: Relevant studies were identified through searching PubMed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure, Wanfang, and VIP databases. Besides, the references of the included studies as a supplementary search were screened. We extracted the basic information of the articles and the outcome information. Two reviewers independently selected the studies and extracted the data. Outcomes were extracted and grouped into domains. Then, semi-structured interview based on the potential factors collected by the systematic review were conducted at West China Second Hospital of Sichuan University. Pregnant women met the diagnostic criteria for PROM were enrolled. Participants were asked about what outcomes they concerned. Two researchers identified the pregnant women concerned outcomes. Results: A total of 90 studies were enrolled in this systematic review. The median number of outcomes in the included studies was 7, with the range 1 to 31. A total of 109 different unique outcomes were identified, of which 40 were maternal outcomes,and 69 were neonatal outcomes. Physiological domain was the most common for both maternal and neonatal outcomes. 47.7 % outcomes were only reported once in the including studies. Thirty pregnant women took part in the semi-structured interviews. 10 outcomes were extracted after normalized, and the outcomes were covered by outcomes reported in the systematic review. But some outcomes concerned by pregnant women were rarely reported in studies. Conclusion: There was considerable inconsistency in outcomes selection and reporting in studies about antibiotics in PROM. An initial outcomes list of a core outcomes set for antibiotics in PROM is formed.